Synthetic transformation of 6-Fluoroimidazo[1,2-a]Pyridine-3-carbaldehyde into 6-Fluoroimidazo[1,2-a]Pyridine-Oxazole Derivatives: In vitro urease inhibition and in silico study - Rafaqat Hussain; Wajid Rehman; Fazal Rahim; Ayman M. Mahmoud; Mohammed M Alanazi; Shoaib Khan; Liaqat Rasheed; Imran Khan (Elsevier, 2023)
Purpose: Ulcer is a serious disease that is caused due to different bacteria and over usage of various NSAIDs which caused to reduce the defensive system of stomach. Therefore, some novel series are needed to overcome these issues. Methods: Oxazole-based imidazopyridine scaffolds (4a-p) were designed and synthesized by two step reaction protocol and then subjected to urease inhibition profile (in vitro). All the newly afforded analogs (4a-p) were found potent and demonstrated moderate to significant inhibition profile. Results: Particularly, the analogs 4i (IC50 = 5.68 ± 1.66 μM), 4o (IC50 = 7.11 ± 1.24 μM), 4 g (IC50 = 9.41 ± 1.19 μM) and 4 h (IC50 = 10.45 ± 2.57 μM) were identified to be more potent than standard thiourea drug (IC50 = 21.37 ± 1.76 μM). Additionally, the variety of spectroscopic tools such as 1H NMR, 13C NMR and HREI-MS analysis were employed to confirm the precise structures of all the newly afforded analogs. Discussion: The structure-activity relationship (SAR) studies showed that analogs possess the substitution either capable of furnishing strong HB like -OH or had strong EW nature such as -CF3 & -NO2 groups displayed superior inhibitory potentials than the standard thiourea drug. A good PLI (protein-ligand interaction) profile was shown by most active analogs when subjected to molecular study against corresponding target with key significant interactions such as pi-pi stacking, pi-pi T shaped and hydrogen bonding.